Causal factors and treatment outcome of genitourinary fistula in a teaching hospital - Fatema, Muckti Kaniz; Saha, Eti; Begum, Fouzia; Lucky, Shamsun Nahar; Rahman, Farzana (Bangladesh Medical Journal Khulna, 2018)
Background: Urogenital fistula, majority of which is vesicovaginal fistula is a public health problem especially of developing countries. It is commonly caused by prolonged and obstructed labor. With the advancement of health care delivery system etiology of urogenital fistula is changing in our country. Objective: This study was done to find out the causal factors and to determine the success rate of operative procedure for treatment of urogenital fistula. Method: This was an observational type of cross sectional study, carried out in Department of Obs and Gynae in Khulna Medical College Hospital from January 2013 to June 2014 among 30 women at different ages suffering from urogenital fistula due to gynaecological or obstetrical causes or malignancy. Result: Majority of the patients were young primipara, short stature and malnourished, coming from lower socioeconomic condition of rural areas. Prolonged labor 12 (40%) was the most common cause of urogenital fistula, followed by gynaecological surgeries mainly hysterectomies 9 (30%) and malignancy 2 (6.6%) rare cause. The success rate of repair following first and second attempt was 92% and 8% respectively. Overall success rate was 24 (96%) and functionally failed with a failure in 1 (4%) cases. This study showed main cause for developing fistula showing prolonged labor and majority of patient were treated pervaginally. Most of the cases (96%) had successful repair which is very encouraging and correlates well with recently published series. Conclusion: Fistula can be totally preventable by proper antenatal care, identification of high risk cases, timely referral, proper intranatal, postnatal care, and proper training. So improvement of health care services and dedication will prevent this type of morbidity. The best results are obtained when repair of urogenital. fistulae is carried out under optimal conditions. Bang Med J (Khulna) 2017; 50 : 18-21